A new species of Contarinia (Diptera: Cecidomyiidae) from flower galls on the relict tree Zelkova abelicea (Ulmaceae) endemic to Crete (Greece) - Fazan, Laurence; Dorchin, Netta; Giriens, Sophie; Pasta, Salvatore; Garfì, Giuseppe; Remoundou, Ilektra; Petrakis, Panos V.; Kozlowski, Gregor (Zootaxa, 2023)
Contarinia ampelitsiae n. sp. Dorchin & Fazan is described as a newly discovered gall-midge species (Diptera: Cecidoymiidae) forming galls in flowers of Zelkova abelicea (Ulmaceae), a tree species endemic to the Mediterranean island of Crete (Greece). Larvae develop within modified filaments of male flowers, contrary to many Contarinia species that develop freely in flowers or in simple flower galls. The species has one generation per year, and its galls are sometimes found in great numbers on individual trees, thus affecting both fruit quantity and weight. This is the first report of a gall midge from Zelkova and the first record of Contarinia from Ulmaceae. Based on its host-plant association and on the barcoding section of the mtCOI gene, this species has no obvious relatives within Contarinia.